2022
DOI: 10.3389/fphar.2022.842730
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyldopamine Dimer Attenuates DSS-Induced Ulcerative Colitis by Suppressing NF-κB and MAPK Pathways

Abstract: Ulcerative Colitis (UC) is a major form of chronic inflammatory bowel disease of the colonic mucosa and exhibits progressive morbidity. There is still a substantial need of small molecules with greater efficacy and safety for UC treatment. Here, we report a N-acetyldopamine dimer (NADD) elucidated (2R,3S)-2-(3′,4′-dihydroxyphenyl)-3-acetylamino-7-(N-acetyl-2″-aminoethyl)-1,4-benzodioxane, which is derived from traditional Chinese medicine Isaria cicadae, exhibits significant therapeutic efficacy against dextra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…To investigate the potential inflammation-related mechanism of 1 , K-means clustering was adopted to assign genes to 2 clusters (A and B) ( Ge et al, 2018 ). After GO analysis, cluster B, which contains 7885 genes, was thought to be closely associated with inflammation ( Supplementary Figure S13 ), and GO analysis and KEGG analysis based on gene set enrichment analysis (GSEA) were performed ( Subramanian et al, 2005 ; Huang et al, 2022 ). The results of GO_GSEA indicated that 1 could reverse the LPS-induced upregulation of three biological processes, including cellular response to molecules of bacterial origin, cellular response to lipopolysaccharide, and lipopolysaccharide-mediated signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the potential inflammation-related mechanism of 1 , K-means clustering was adopted to assign genes to 2 clusters (A and B) ( Ge et al, 2018 ). After GO analysis, cluster B, which contains 7885 genes, was thought to be closely associated with inflammation ( Supplementary Figure S13 ), and GO analysis and KEGG analysis based on gene set enrichment analysis (GSEA) were performed ( Subramanian et al, 2005 ; Huang et al, 2022 ). The results of GO_GSEA indicated that 1 could reverse the LPS-induced upregulation of three biological processes, including cellular response to molecules of bacterial origin, cellular response to lipopolysaccharide, and lipopolysaccharide-mediated signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The primary antibodies were as follows: TLR4 (1:4000; Proteintech, Rosemont, USA), NF-κB (1:1000; CST, Beverly, USA), NLRP3 (1:1000; CST), Caspase-1 (1:1000; Proteintech), ASC/TMS1 (1:1000; Proteintech), iNOS (1:1000; NOVUS, Littleton, USA), COX-2 (1:1000; Abcam, Cambridge, UK), and β-Actin (1:20,000; Proteintech). Then, the PVDF membranes were incubated with the corresponding HRP-conjugated secondary antibodies at room temperature for 2 h. Finally, the membranes were washed 3 times with PBS, the target proteins were visualized using Immobilon western chemiluminescent HRP substrate (Millipore, Billerica, USA), and the blot images were captured and analyzed with the Chemiluminescent Imaging System (SAGECREATION, Beijing, China ) [16] .…”
Section: Methodsmentioning
confidence: 99%
“…N-acetyldopamine dimer (NADD) is a natural compound and has been elucidated as (2R,3S)-2-(3′,4′-dihydroxyphenyl)-3- acetylamino-7-(N-acetyl-2″-aminoethyl)-1,4-benzodioxane. In our previous study, NADD extracted from the traditional Chinese medicine Isaria cicada was found to suppress inflammation in DSS-induced ulcerative colitis by inhibiting the NF-κB and MAPK signaling pathways [16] . In addition, NADD has been reported to possess antioxidant and anti-inflammatory activities [17] .…”
Section: Introductionmentioning
confidence: 97%
“…Dextran sulfate sodium (DSS) has been used widely to generate an experimental model of UC disease. The clinical phenotype of the animal model shares a high similarity with that of patients with UC ( 5 , 29 31 ).…”
Section: Introductionmentioning
confidence: 99%